Comparison of the European Union’s Markets in Crypto-Assets Regulation and the United States’ Enforcement-Based Approach to Crypto-Asset Regulation - Laucius, Gediminas (Teisė, 2025)
The rapidly evolving industry of crypto-assets presents significant regulatory challenges, which are further complicated by differing approaches in the European Union (EU) and the United States (US). This article compares these frameworks, while focusing on the EU’s Markets in Crypto-Assets (MiCAR) and the US’s Regulation by Enforcement strategies.The EU takes a proactive approach through its MiCA regulation, set to take effect on December 30, 2024. This regulation aims to harmonize the EU’s regulatory framework for crypto-assets and crypto-asset service providers (CASPs), by virtue of offering legal clarity and creating a stable environment for digital assets, and thus ensuring consumer protection similar to the traditional financial sector.Conversely, the US adopts a reactive stance, by applying the already existing legal rules to crypto-assets under the principle of technological neutrality. This ‘regulation by enforcement’ approach relies on established legal principles and regulatory discretion, while raising challenges related to legal predictability, supervisory powers, and the adaptation of the traditional laws to new technologies.The comparative analysis conducted in this article explores practical regulatory challenges and broader implications for consumer protection, market stability, legal predictability and innovation incentives. By examining these elements, it contributes to the discourse among scholars and young researchers in the field of legal innovation.
Keywords: crypto-assets; regulatory frameworks; Markets in Crypto-Assets Regulation (MiCAR); technological neutrality; regulation by enforcement; Crypto-Asset Service Providers (CASPs)